Exosomes and Melatonin: Where Their Destinies Intersect - Novais, Adriana Alonso; Chuffa, Luiz Gustavo de Almeida; Zuccari, Débora Aparecida Pires de Campos; Reiter, Russel J. (Frontiers in Immunology, 2021)
Cell-to-cell communication is a broad and complex process associated with regular stimuli to maintain healthy cell interactions. One of the agents capable of cellular communication is known as an exosome, a subset of extracellular vesicles (EVs) released by the cell membrane. The exosome contains a wide range of functional proteins, mRNAs and miRNAs, which have the potential to interact with healthy or diseased cells in the body. On the other hand, melatonin also acts as a cellular communicator, produced and released by the pineal gland in a circadian way and also, non-circadian melatonin is derived from the mitochondria of all normal cells. In addition to exhibiting antioxidant, anti-inflammatory, anti-tumor and anti-aging activities, melatonin has recently been studied by its influence on exosomes. This review summarizes the relationship between exosomes and melatonin in various pathological processes. There is robust evidence that their combination ameliorates inflammation, ischemia-reperfusion injury, hepatic metabolic disturbance, cancer immunosuppression status, degenerative processes like chronic kidney disease, vascular calcification, ageing, ischemic brain injury, neurodegenerative diseases, obesity, colitis, wound healing and even embryonic development. Association of exosomes and melatonin represent a promising therapeutic tool, capable of interfering with basic molecular processes, such as oxidative stress and the inflammatory cascade, which support many pathophysiological aspects of diseases.